Management of Religious Moderation Learning in the Independent Curriculum: A Kindergarten Case Study (THUFULA, 2025)
The aim of this research is to describe and analyze religious moderation learning management activities in the independent curriculum in kindergarten. This research uses a qualitative approach with a phenomenological type of research. Data was collected using interview, observation and documentation techniques. Then it was analyzed using the Miles and Huberman model data analysis technique which consists of data reduction, data display and verification. Based on the research results, it can be seen that teachers carry out four management activities for religious moderation learning in the independent curriculum in kindergarten, namely planning, organizing, implementing and assessing religious moderation learning in the independent curriculum. In planning religious moderation learning in the independent curriculum, teachers develop religious tolerance teaching modules. This teaching module is used as a guide in implementing religious moderation learning. Then, in organizing religious moderation learning, the teacher coordinates to discuss religious moderation materials that will be given to children, procurement of tools and materials for religious moderation learning, as well as the types of activities that will be given to children to internalize the value of religious tolerance in children. Meanwhile, the implementation of religious moderation learning is carried out through the knowledge transformation stage about religious moderation, the play stage with the theme of religious moderation, the literacy stage with the theme of religious moderation and the reflection stage. Then proceed with assessing religious moderation learning using observation and documentation techniques. In the observation technique, anecdotal notes and check lists are used. In the documentation technique, work instruments and series of photographs are used.